VD_FINDINFO Arrêt / 2024 / 135 vom 14. März 2024 - VD Tribunal cantonal (2024)
DROIT D'ÊTRE ENTENDU, REJET DE LA DEMANDE, EXPERTISE MÉDICALE, FORCE PROBANTE | 28 al. 1 LAI, 28 al. 2 LAI, 4 al. 1 LAI, 57a LAI, 17 al. 1 LPGA, 8 al. 1 LPGA, 87 al. 2 RAI, 87 al. 3 RAI